Development Of A Website Based On A Contextual Approach As A Biology Learning Media On The Subconcept Of The Human Sensory System - Herliana Juliyanti; Mila Ermila Hendriyani; Mahrawi Mahrawi (Universitas Tidar, 2022)
This study aims to develop a website based on a contextual approach to the sub-concept of the human sensory system. The method used in this research is research and development. This study used Sugiyono's research design. The research was carried out in May 2022 at Universitas Sultan Ageng Tirtayasa and SMAN 1 Kabupaten Tangerang. The subjects in this study were two material experts, two media experts, and users (teachers and students). In this study, samples of teachers and students were taken from one biology teacher in class XI and ten students in class XI at SMAN 1 Kabupaten Tangerang. The product validation results from media experts got an average value of 93.3%. From material experts, the average score is 97.1%. The teacher's response test result got an average value of 96.2%, and the student response test got an average value of 91.4%. These results indicate that a website based on a contextual approach to the human sensory system's sub-concept falls into a very feasible category for use in learning activities.